2016
DOI: 10.4067/s1726-569x2016000200016
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos Bioéticos da Judicialização da Saúde por Medicamentos em 13 Municípios no Meio-Oeste de Santa Catarina, Brasil

Abstract: Resumo: A judicialização na saúde é um fenômeno recente no Brasil, com sérias repercussões no sistema de saúde público brasileiro. O objetivo deste trabalho foi estudar sua ocorrência em treze municípios de pequeno porte no Meio-Oeste de Santa Catarina, sul do Brasil, no período de 2007 a 2012, analisar os aspectos bioéticos relacionados e propor soluções. Os resultados evidenciaram que, neste período, o valor total/ano das demandas judiciais por medicamentos aumentou quase 10 vezes, beneficiando apenas 175 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
19

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 3 publications
(4 reference statements)
0
4
0
19
Order By: Relevance
“…In addition, there are still difficulties in meeting collective health needs, which may be related to the complex concept of the "existential minimum". [3][4][5][6] When analyzing the decrease in lawsuits in the year 2013, as in shown in table 1, it was observed that this does not result from a real reduction in the number of lawsuits, but from a strategy used by the internal processes service instituted in DRS XIII, called administrative processes. This strategy serves to stimulate the agreements between the Public Prosecutor's Office, the Public Defender's Office and those responsible for the pharmaceutical assistance of the State and the Municipality to administratively seek a solution to reduce the legal demands.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, there are still difficulties in meeting collective health needs, which may be related to the complex concept of the "existential minimum". [3][4][5][6] When analyzing the decrease in lawsuits in the year 2013, as in shown in table 1, it was observed that this does not result from a real reduction in the number of lawsuits, but from a strategy used by the internal processes service instituted in DRS XIII, called administrative processes. This strategy serves to stimulate the agreements between the Public Prosecutor's Office, the Public Defender's Office and those responsible for the pharmaceutical assistance of the State and the Municipality to administratively seek a solution to reduce the legal demands.…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of lawsuits filed by the plaintiff represents a relevant indicator in the evaluation of such lawsuits. 6 In analyzing the representation of the plaintiff, 431 (67.7%) were represented by Public Judicial Institutions, of which 402 (63.2%) were the Public Prosecutor's Office and 29 (4.5%) were the Public Defender's Office (Table 2). Thus, there was a predominance of actions filed by Judicial Institutions which is in line with other studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Uma das ações foi ajuizada pelo Ministério Público (MP) do Pará, por meio de uma Ação Pública 14 . Nela, o MP ordenou ao estado do Pará que fornecesse a somatropina, conhecida como hormônio do crescimento, a todas as crianças e adolescentes com deficiência na produção de somatropina, motivados pela falta de fornecimento do hormônio pelo SUS.4.1.1 Ações para obtenção de medicamentosPercebe-se que há diversos estudos10,[15][16][17][18][19][20][21][22][23][24][25][26][27] que investigam as ações judiciais para obtenção de medicamentos ou tratamentos. Os usuários do SUS estão em maioria como solicitantes.…”
unclassified